Conveyor Belt Object Identification: Mathematical, Algorithmic, and Software Support - Nevliudov, I. Sh; Yevsieiev, V. V.; Maksymova, S. S.; Omarov, A. O. M.; Klymenko, O. M. (Natural Sciences Publishing (NSP), 2023)
This article is devoted to the development of a package identification system on a mixed conveyor sorting line with a vertical lift from Kapelou. In the conditions of modern Warehouse 4.0 systems requirements, a tasks number arise associated with automatic objects sorting in real time. One of the most common is QR codes using, as it is the most costeffective. But the introduction of automated systems for identifying objects on a conveyor line based on QR codes causes a number of tasks that are associated with the dynamic parameters of identifying the location of the package in the recognition zone, determining and localizing the location of the QR code, for further reading and decoding information about the package with further adoption decisions about its movement in the sorting system. The authors propose a solution to this problem by developing a module for identifying and recognizing objects on a conveyor line based on computer vision using a Raspberry Pi 4 Model B single-board computer with a developed method for processing a QR code image, the system structure, algorithmic and mathematical support have been developed. To check the correctness of proposed decisions, software was developed, and a number of natural experiments were carried out with different parameters (conveyor speeds, illumination, packaging feeding angles for the computer vision system) for the developed object identification system on the Kapelou sorting conveyor line, which showed a high processing speed and decoding data from a QR code.
Keywords: Conveyor Belt; Object Indentification; Object Recognition; Raspberry Pi; QR-code